Edukasi Pemanfaatan Gonad Bulu Babi (Diadema setosum) sebagai Jajanan Sehat - Hariani, Hariani; Fathurrahman, Teguh; Wiralis, Wiralis; Imanuddin, Imanuddin; Suwarni, Suwarni; Sudarsono, I Made Rai (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
The availability of unhealthy snacks in school environments poses a challenge in efforts to improve children's nutritional quality and prevent stunting. Utilizing locally available nutrient-rich food sources, such as sea urchin gonads (Diadema setosum), can serve as a safe and nutritious alternative for school snacks. This community engagement initiative aims to enhance the knowledge and skills of housewives, school canteen operators, and Posyandu (integrated health post) cadres in processing sea urchin gonads into healthy snacks for school children. The training involved 20 participants from Waworaha and Soropia Villages, Soropia District, Konawe Regency. The methods employed included lectures, discussions, and demonstrations on the preparation of locally sourced nugget and siomay. Evaluation results indicated an average increase of 30% in participants' knowledge scores based on pre-test and post-test assessments. Participants also demonstrated the ability to apply the skills acquired during the training. This initiative not only raises awareness of the importance of balanced nutrition but also promotes the utilization of local resources as part of food diversification efforts. Contribution to Sustainable Development Goals (SDGs) This initiative contributes to Sustainable Development Goals (SDGs) Target 3.4, which aims to reduce mortality from non-communicable diseases and promote mental health through prevention and health promotion efforts. Overall, this activity aligns with SDG Goal 3: Good Health and Well-Being, which seeks to ensure healthy lives and promote well-being for all ages. Additionally, this initiative supports SDG Goal 2: Zero Hunger, particularly Targets 2.1 and 2.2, which focus on improving food security and ensuring balanced nutrition, including stunting prevention among children.